Terrestrial prey inputs to streams bordered by deciduous broadleaved forests, conifer plantations and clear‐cut sites in southwestern Japan: effects on the abundance of red‐spotted masu salmon. Issue 3 (9th January 2013) - Inoue, Mikio; Sakamoto, Shogo; Kikuchi, Shugo
Abstract: Terrestrial invertebrates falling from the riparian canopy are a major energy source for fishes in headwater streams. Because quantity and quality of such allochthonous resources can vary depending on riparian conditions, conversion of riparian forests to conifer plantations may affect stream productivity. We compared falling and drifting invertebrate abundances and the diet of masu salmon ( Oncorhynchus masou ) among stream reaches bordered by deciduous broadleaved forests, conifer plantations ( Cryptomeria japonica ), and clear‐cut sites in southwestern Japan. We also examined whether among‐reach variation in salmon abundance was related to the riparian vegetation types. The results indicated that, on an annual basis, falling inputs of terrestrial invertebrates at the broadleaved reaches were 2–4 times higher than those at the plantation and clear‐cut reaches. In nonwinter seasons, terrestrial invertebrates made up 40–60% and 30–90% of drift and masu salmon diets, respectively, and drifting invertebrate abundance was higher in the broadleaved reaches than in the plantation reaches. Furthermore, a multivariate analysis of salmon abundance showed that variation in salmon biomass was explained primarily by riparian vegetation type, with broadleaved and clear‐cut reaches having higher biomass than the plantation reaches. These results indicate that terrestrial invertebrates are an important resource for masu salmon, and suggest that streams bordered by conifer plantations receive lower terrestrial prey inputs, which results in lower salmon abundance. In regions where natural forests have been extensively converted to conifer plantations, forest management that allows and facilitates recovery of natural riparian stands is important.